ASSISTANCE FOR THE PREPARATION OF THE PETUNGSEWU BUMDES REVIVAL STRATEGY - Oktavendi, Tri Wahyu; Widyastuti, Aviani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This service aims to assist BUMDes so they can find out village potential that can be developed. The mentoring method is carried out starting from the FGD to collect various inputs and evaluations on the BUMDes DAU. After that, a field survey was assisted by the Student PMM Team to find out the real condition of BUMDes. Finally, mentoring is carried out to solve all existing problems. The results of this service are several strategies that can be offered to improve the management of BUM Desa Petungsewu, including that BUM Desa needs to develop strategic partnerships in the form of BUMDes cooperation between villages or cooperation with the private sector. Therefore, the Matching Fund Program will be very helpful for the success of this strategy.